"Placebo effect is probably what we refer to as patient healing power": A qualitative pilot study examining how Norwegian complementary therapists reflect on their practice - Trine Stub; Nina Foss; Ingrid Liodden (BMC, 2017)
Abstract Background Complementary therapists spend considerable time with their patients, especially in the first consultation. The communication between patients and their therapists is important for raising consciousness and activation of the patient's self-healing power. Thus, the aims in this study were to delineate what complementary therapists regard as essential in patient consultations, their view of the healing process, and how the therapists understand the placebo effect and its position in the healing process. Methods Semi-structured individual interviews (n = 4), focus group interview (n = 1) and participant observation were conducted among four different complementary therapists in a Norwegian community. The text data was transcribed verbatim and the analysis of the material was conducted according to conventional and direct content analysis. Some codes were predefined and others were defined during the analysis. Results The pilot study showed that the implemented methods seems feasible and fit well with the aims of this study. Complementary therapists (chiropractor, naprapath (musculoskeletal therapist), acupuncturist and acupuncturist/homeopath) representing four different complementary modalities participated. A combination of the conversation and examination during the first consultation formed the basis for the therapist's choice of treatment. A successful consultation was characterized by a fruitful relationship between the therapist and the patient. Moreover, the therapist needs to be humble and show the patient respect. Patients' positive beliefs and expectations about the treatment play a significant role in the healing process. The more hope the therapist can bring about, the more easily the patient can start believing that it is possible to get well. Conclusion This was a pilot study. Therefore the findings should be appreciated as limited and preliminary. Therapists' and patients' mutual understanding and treatment goals were essential for a successful consultation. The therapists emphasized their professional skills and therapeutic competence as important when building fruitful relationships with their patients. Exerting authority and making the patient feel confident were essential factors for a successful healing process. The complementary therapists understood the placebo effect as the patient's self-healing power, resulting from establishing trust and belief in the treatment process.